Adjustable electromagnetically induced transparency effect based on graphene surface plasmon. (April 2019) - Li, X.; Xie, R.; Li, W.; Li, Z.; Gu, E.; Niu, L.; Guo, S.
Abstract: In this paper, the electromagnetically induced transparency (EIT) effect of graphene nanostructures was studied by numerical methods. Numerous branch structures were added to the sides of the graphene/medium/graphene waveguide, and the Fabry-Perot resonators were formed between adjacent branches due to the phase coupling effect. The back and forth oscillation of electromagnetic waves in the cavity significantly enhanced the transmitted light in a narrow band. Thus, an output spectrum similar to the EIT effect was produced. The output spectrum can be further adjusted by the gate voltage with the unique electrically adjustable properties of graphene. The surface of plasmon exhibited stronger locality in graphene nanostructures than metals. Thus, graphene-based electro-optical devices were more compact and integrated in the deep sub-wavelength scale. The proposed graphene nanostructures facilitated the implementation of a variety of high performance electro-optical devices, including multi-channel selective filters, sensors, and modulators. Highlights: The EIT effect of graphene nanostructures was studied by numerical methods. The Fabry-Perot resonators were formed between adjacent branches. The surface plasmons exhibited stronger locality in graphene nanostructures than metals. The structures facilitate the implementation of high performance electro-optical devices.